2004
DOI: 10.1093/ndt/gfh094
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced acute renal failure associated with renal hypouricaemia: results of a questionnaire-based survey in Japan

Abstract: The reason for the heterogeneity in ARF associated with renal hypouricaemia remains unknown. Further studies, especially on molecular mechanisms, are required to establish the best guidance against ARF recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 20 publications
2
95
0
2
Order By: Relevance
“…26 It is thus possible that the lack of UA in plasma of patients with hereditary hypouricemia predisposes them to ischemic acute renal failure. This hypothesis is supported by reported imaging results 27 as well as biopsy results of patients with EIARF showing mainly acute tubular necrosis 28 ; however, EIARF has never been described in patients with xanthinuria, whose serum UA levels are as low as those of patients with renal hypouricemia. We propose a third mechanism for EIARF: Reduced clearance of urate-coupled anions by URAT1 as a result of loss-of-function mutations of either URAT1 or GLUT9 may exert toxic effects on renal proximal tubules, leading to toxic acute tubular necrosis.…”
Section: Transporters (mentioning
confidence: 69%
“…26 It is thus possible that the lack of UA in plasma of patients with hereditary hypouricemia predisposes them to ischemic acute renal failure. This hypothesis is supported by reported imaging results 27 as well as biopsy results of patients with EIARF showing mainly acute tubular necrosis 28 ; however, EIARF has never been described in patients with xanthinuria, whose serum UA levels are as low as those of patients with renal hypouricemia. We propose a third mechanism for EIARF: Reduced clearance of urate-coupled anions by URAT1 as a result of loss-of-function mutations of either URAT1 or GLUT9 may exert toxic effects on renal proximal tubules, leading to toxic acute tubular necrosis.…”
Section: Transporters (mentioning
confidence: 69%
“…7 The antioxidative role of SUA is also supported by the observation of acute kidney injury in patients with renal hypouricemia after strenuous exercise, possibly related to renal vasoconstriction. 8 Similarly, a beneficial role of UA in the nervous system has been suggested, as patients with multiple sclerosis and Parkinson's disease have significantly lower SUA than healthy controls. 9 Hypouricemia is arbitrarily defined as a SUA concentration <2-3 mg/dl.…”
Section: Editorial Effect Of Ua On Vascular Functionmentioning
confidence: 97%
“…However, a recent study reported that subjects having the common nonsense mutation, W258X, which is responsible for renal hypouricemia, showed significantly reduced renal function independently of age, sex, BMI, hypertension, and serum uric acid levels [8]. In addition, renal hypouricemia is known to be associated with two complications, acute kidney injury (AKI) [9,10] and nephrolithiasis [10,11]. Because both AKI and urolithiasis are risk factors for reduced kidney function [12,13], we hypothesized that individuals with hypouricemia may be at greater risk of reduced kidney function.…”
Section: Introductionmentioning
confidence: 99%